Working Desks as a Classification Tool for Personality Style: A Pilot Study for Validation - Render, Anna; Siebertz, Markus; Günther, Bianca; Jansen, Petra (Frontiers in Psychology, 2019)
We shape our surroundings; form the rooms we live in, so that we feel comfortable in them. This shows parts of our personality – it can be inferred from our environment. In this study, we created stereotypical desks embodying different personality styles and let 190 students choose which desk fits – in their subjective perspective - the most to their personality. To determine their personality style, the Personality Style and Disorder Inventory (PSSI) was used. Correspondence analysis was conducted to investigate the relationship between personality styles and choice of desks. Results did not show convergence of personality styles and desks. Contrary to the popular scientific idea, personality and creation of surroundings were not related; regarding our study, the relation is uninterpretable suggesting an individual’s desk choice is not statistically dependent on one's individual’s highest PSSI subscale. The study can be regarded as a pilot project for desk designs as classification tool for personality.